Trend of Anemia Prevalence in Pregnant Women in the Working Area of Sukosari Health Center, Madiun City, 2018-2022 - Nur Heliana Sari; Heru Santoso Wahito Nugroho; Tinuk Esti Handayani; Teta Puji Rahayu (Knowledge Dynamics, 2024)
Pregnancy anemia poses a significant national challenge due to its adverse impact on human resource (HR) quality. Without proper management, it can lead to maternal and fetal complications, even death. This study aimed to determine the trend of anemia prevalence of pregnant women from 2018-2022 in the working area of Sukosari Health Center, Madiun City. Conducted as descriptive quantitative research with predictive elements, it encompassed 2157 pregnant women in the center's jurisdiction. Utilizing the total population as the sample, data was collected from maternal LB3 documents. Trendline analysis in MS Office Excel revealed the trend and prediction of the anemia prevalence in the following year by displaying the equation display on chart. The results showed a trend and prediction of the anemia prevalence for pregnant women at the end of 2023, the total Sukosari Health Center increased. The trend and prediction of the prevalence of pregnant women in each village and each trimester of pregnancy also increased. The highest increase in the anemia prevalence for pregnant women occurred in Klegen Village and in the first trimester of pregnancy. From these results, it can be concluded that the trend of anemia prevalence of pregnant women at the health center has increased and exceeds the target set by the Madiun City Health Office, which is <15%. This condition needs to be monitoring and paid special attention to by increasing education on the prevention and treatment of anemia among adolescent girls and pregnant women, monitoring and evaluating the program of giving blood-added tablets, and maximizing local area monitoring of pregnant women. Innovative efforts can also be made in the form of taking blood tablets together on the opening day of pregnancy check-up services and during the implementation of classes for pregnant women and organizing classes for brides-to-be at health centers.